Amorphous Silicon Nanoparticles and Silicon Nanoglasses From Ab Initio Simulations - Bolat, Suleyman; Durandurdu, Murat (Springer, 2024)
The structural and electrical characteristics of spherical amorphous silicon nanoparticles (Si-NPs) with radii ranging from 9 to 15 & Aring;, and silicon nanoglasses (Si-NGs) formed by compressing identical-sized Si-NPs, are being investigated for the first-time using ab initio simulations. Analysis reveals predominantly fourfold coordination within Si-NPs, accompanied by noticeable coordination defects. The prevalence of fourfold coordination increases with increasing Si-NP size. Si-NGs, while exhibiting similar dominant fourfold coordination, possess a small fraction of coordination defects (5-8%) primarily concentrated at the interfaces of compressed Si-NPs. Si-NGs are found to have a more open structure compared to amorphous Si. This structural variation, along with observed distortions within Si-NGs, is hypothesized to contribute to a significant narrowing of their band gaps relative to amorphous Si.
Keywords: Amorphous; Silicon; Nanoglass; Nanoparticle; High Pressure